Influence of the application of the modern taxing administration system, taxing awareness, and tax sanctions regarding the compliance in yearly tax report for annual individual tax income (a study case on employees of PT. Tritanu Hub’s Indonesia, PT. Samiplast Joyo Mandiri and PT. Armuh Global Management) - Catherina Catherina; Juitania Juitania (IDEAS: Journal of Management & Technology, 2021)
This research aims to determine the effect of the application of the modern tax administration system, tax awareness and tax sanctions on the compliance of individual taxpayers' annual income tax returns. The independent variable in this research is represented by (1) Application of Modern Tax Administration System, (2) Tax Awareness, (3) Tax Sanctions. This type of research is quantitative research. The population in this research are individual taxpayers who report their annual income tax return. The sampling technique used in this study was purposive sampling technique. The sample is 53 out of 112 taxpayers on employees of PT. Tritanu Hub’s Indonesia, PT. Samiplast Joyo Mandiri and PT. Armuh Global Management. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of this research, it is found that (1) Implementation of Modern Tax Administration System, (2) Tax Awareness, (3) Tax Sanctions simultaneously affect Compliance with Individual Taxpayer Annual Income Tax Reporting Compliance. Partially, it is found that (1) The implementation of the Modern Tax Administration System and (2) Tax Awareness have a significant effect on the Compliance of the Annual Income Tax Return of Individual Taxpayers. The greater the variables (1) Implementation of the Modern Tax Administration System and (2) Tax Awareness will cause a high level of Compliance with Individual Taxpayer Annual Income Tax Reporting. Partially obtained, (3) Tax Sanctions don’t have an effect on the Compliance of the Annual Income Tax Return Report of Individual Taxpayers.